PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI MODEL PROBLEM BASED LEARNING MENGGUNAKAN MEDIA CONGKLAK - Suryadi, Suryadi; Nurasiah, Iis; Khaleda Nurmeta, Irna (Jurnal Pendidikan Dasar, 2023)
Abstract: Low learning motivation, an unattractive learning atmosphere, loss of student focus while studying, and the learning media used are not innovative, making the learning outcomes of fourth grade students low . Efforts are being made to overcome this by applying the traditional congklak game-based learning method to learning mathematics. The expected goal of this research is to increase students' critical thinking skills which include planning, implementation, constraints, and results towards increasing students' critical thinking skills. This research was conducted using the Kemmis and Mc Taggart models. The findings from the research conducted show that the planning process is carried out by determining the TP, compiling teaching modules by applying the problem-based learning model using congklak media, and preparing research instruments. The implementation process is carrying out learning in accordance with the plans that have been prepared and data collection is carried out during the implementation process. The results obtained from the research show that students' critical thinking skills have increased from each cycle. In the first cycle, students' critical thinking skills reached an average percentage of 57.92% which was converted to the sufficient category, and in the second cycle, students' critical thinking skills achieved an average percentage of 75.97% which was converted to the good category. Keyword : critical thinking, problem based learning, congklak